Adoptive Parenting Cognitions: Acknowledgement of Differences as a Predictor of Adolescents' Attachment to Parents. (2nd April 2020) - Lo, Albert Y. H.; Grotevant, Harold D.
SYNOPSIS: Objective . Adoptive parents' acknowledgment of differences is defined as the propensity to think that adoptive and nonadoptive families are different in important ways. Few studies have examined the implications of such cognitions for the parent–child bond. Design . Structural equation modeling was utilized to examine the relation between adoptive parents' acknowledgment of differences and adolescents' later attachment to their parents in a sample of within-race domestic infant adoptions. Data from 189 adoptive families were drawn from two waves (middle childhood, adolescence) of the Minnesota/Texas Adoption Research Project, a longitudinal study of openness in adoption. Results . Levels of acknowledgment of differences displayed by the adoptive mother and adoptive father during middle childhood positively predicted adopted adolescents' feelings of attachment toward the respective parent 8 years later. This relation depended on adopted adolescents' attitude toward adoption-related communication during middle childhood as well as the adoptive family's level of openness during middle childhood. Conclusions . Acknowledgment of differences in adoptive families has positive implications for the parent–child bond.